2009
DOI: 10.1159/000202988
|View full text |Cite
|
Sign up to set email alerts
|

Pyloric Neuron Morphology in the Stomatogastric Ganglion of the Lobster, <i>Panulirus interruptus</i>

Abstract: The pyloric network of decapod crustaceans has been intensively studied electrophysiologically in the infraorders Astacidea, Brachyura, and Palinura. The morphology of some or all pyloric neurons has been well described in Astacidea and Brachyura, but less so in Palinura. Given the large evolutionary distance between these three groups, and the large amount of electrophysiology that has been performed in palinuroid species, it is important to fill this gap. We describe here the gross morphology of all six pylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 102 publications
5
23
0
Order By: Relevance
“…Consistent with a previous report (Thuma et al, 2009), the length and trajectory of the primary neurite varied, possibly due to different soma locations (e.g., anterior vs. middle vs. posterior region of the STG) and the need for the primary process to extend throughout the neuropil. Each PD neuron had 9–10 secondary branches arising from the primary neurite.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with a previous report (Thuma et al, 2009), the length and trajectory of the primary neurite varied, possibly due to different soma locations (e.g., anterior vs. middle vs. posterior region of the STG) and the need for the primary process to extend throughout the neuropil. Each PD neuron had 9–10 secondary branches arising from the primary neurite.…”
Section: Resultssupporting
confidence: 90%
“…These, in turn, can continue to divide beyond the 16th branch order (see below), ultimately generating small-diameter processes. The large-diameter processes are in the central core of the ganglion (coarse neuropil), whereas the higher order branches reside in the fine neuropil layered between the coarse neuropil and somata (Thuma et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…That said, at a finer scale of analysis, intracellular dye-fills of identified neurons in invertebrates show clear evidence of animal-to-animal variations in soma positions and branching patterns [27, 28, 29]. For example, a recent study of the Anterior Gastric Receptor (AGR) neuron in the crab stomatogastric ganglion (STG) shows large variations in the number of branches that AGR makes in the STG neuropil [28].…”
Section: Variability In System Components Across Animalsmentioning
confidence: 99%
“…The California spiny lobster Panulirus interruptus has long served as an important animal model for many areas of research in endocrinology and neurobiology [22-24], but its genome has not been sequenced yet and there is no protein/cDNA database. In particular, its stomatogastric ganglion has been utilized as a powerful model system to understand the cellular mechanisms of rhythmic pattern generation in neuronal networks [22].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, its stomatogastric ganglion has been utilized as a powerful model system to understand the cellular mechanisms of rhythmic pattern generation in neuronal networks [22]. Many studies reported that neurotransmitters and neuropeptides regulate the functional output of these well-defined neuronal circuits [25-28].…”
Section: Introductionmentioning
confidence: 99%